Perioperative enriched environment attenuates postoperative cognitive dysfunction by upregulating microglia TREM2 via PI3K/Akt pathway in mouse model of ischemic stroke - Yao, Yuchen; Hu, Liru; Li, Danni; Wang, Yuhao; Pan, Jian; Fan, Dan (Frontiers in Neuroscience, 2024)
Postoperative cognitive dysfunction (POCD) is a prevalent complication that significantly affects the quality of life. Notably, patients who have experienced ischemic stroke are at an increased risk of developing POCD. Exploring the underlying mechanisms of POCD is crucial for its management. Numerous studies have established neuroinflammation as an independent risk factor in POCD pathogenesis, with TREM2 emerging as a key neuroprotective factor that modulates neuroinflammatory responses through the PI3K/Akt signaling pathway. In this study, we aimed to investigate the effect of TREM2 on POCD in a mouse model of ischemic stroke, with a focus on the mechanisms involving TREM2 and the PI3K/Akt signaling pathway. Our findings indicated that mice with ischemic stroke exhibited severe cognitive impairment after surgical trauma. However, we observed that an enriched environment (EE) could ameliorate this cognitive impairment by upregulating microglia TREM2 expression in the hippocampus and suppressing neuroinflammation. Additionally, the PI3K/AKT signaling pathway was activated in the hippocampal tissue of the mice housed in EE. Importantly, the beneficial neuroprotective and anti-inflammatory effects of EE were abolished when TREM2 was knocked down, underscoring the essential role of TREM2 in mediating the effects of EE on neuroinflammation and cognitive function after ischemic stroke and surgical trauma. In general, our study has confirmed a potential molecular mechanism that led to the occurrence of POCD in individuals with ischemic stroke and provided new strategies to treat POCD.